2013
DOI: 10.1007/s00401-013-1189-3
|View full text |Cite|
|
Sign up to set email alerts
|

Bidirectional transcripts of the expanded C9orf72 hexanucleotide repeat are translated into aggregating dipeptide repeat proteins

Abstract: Massive GGGGCC repeat expansion in the first intron of the gene C9orf72 is the most common known cause of familial frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS). Despite its intronic localization and lack of an ATG start codon, the repeat region is translated in all three reading frames into aggregating dipeptide-repeat (DPR) proteins, poly-(Gly-Ala), poly-(Gly-Pro) and poly-(Gly-Arg). We took an antibody-based approach to further validate the translation of DPR proteins. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
462
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(484 citation statements)
references
References 34 publications
20
462
2
Order By: Relevance
“…Unexpectedly, neurons from cases with the C9orf72 intronic expansion also possess a third type of inclusion: intracytosolic aggregates composed of dipeptide repeat proteins encoded by the intronic hexanucleotide repeat that are produced through noncanonical, repeat-associated non-ATG-mediated (RAN-mediated) translation. These atypical peptides reflect translation of amino acids from all possible reading frames of the G 4 C 2 expanded domains (69)(70)(71)(72)(73). Some RAN-produced peptides, such as those containing repeated arginines, are neurotoxic in flies and mammalian neurons in vitro (74,75) Protein degradation.…”
Section: Protein Toxicity: Protein Aggregation and Prion Domainsmentioning
confidence: 99%
“…Unexpectedly, neurons from cases with the C9orf72 intronic expansion also possess a third type of inclusion: intracytosolic aggregates composed of dipeptide repeat proteins encoded by the intronic hexanucleotide repeat that are produced through noncanonical, repeat-associated non-ATG-mediated (RAN-mediated) translation. These atypical peptides reflect translation of amino acids from all possible reading frames of the G 4 C 2 expanded domains (69)(70)(71)(72)(73). Some RAN-produced peptides, such as those containing repeated arginines, are neurotoxic in flies and mammalian neurons in vitro (74,75) Protein degradation.…”
Section: Protein Toxicity: Protein Aggregation and Prion Domainsmentioning
confidence: 99%
“…Potential pathomechanisms include the loss of function of normal C9orf72 protein, and/or toxicity resulting from the accumulation of G 4 C 2 transcripts that form RNA foci, interact with RNA‐binding proteins, and impair RNA processing 6. Expanded G 4 C 2 transcripts also lead to the production of five dipeptide repeat (DPR) proteins through repeat‐associated non‐ATG (RAN) translation 7, 8. RAN translation of sense transcripts of the repeat produces poly(GA), poly(GR), and poly(GP), while RAN translation of antisense repeat transcripts produces poly(PA), poly(PR), and poly(GP).…”
Section: Introductionmentioning
confidence: 99%
“…39,[83][84][85][86] A genome-wide study in yeast found that RNADNA hybrids are enriched in genes that produce antisense transcripts and that the expression of these genes is regulated by the hybrids. 87 A recent study by Skourti-Stathaki et al reported that R-loops induce antisense transcription, which leads to RNA interference-dependent repressive histone marks over mammalian gene terminators.…”
Section: Histone and Dna Methylationsmentioning
confidence: 99%